Development of graphitic carbon nitride based assemblies for sunlight driven photocatalysis - Hak, Chen Hong (2018)
This present work focused on the development of binary graphitic carbon nitride (g-C3N4) composite for sunlight driven photocatalysis. In the 1st project, the binary composite was achieved by doping noble metals such as gold (Au), silver (Ag) and palladium (Pd) with g-C3N4 through sunlight photodeposition. The deposition of Ag nanoparticles (NPs) (7.5 nm) resulted in the degradation of Bisphenol A (BPA) which was 2.15 fold higher than that of g-C3N4. For 2nd project, carbon dots (CDs) were successfully derived from water hyacinth leaves and the binary composite was achieved by incorporating CDs with g-C3N4 through hydrothermal treatment. The average particle size of CDs was found to be 3.1 nm and a blue-green fluorescence was emitted under the UV light irradiation. Both of 20CDs/g-C3N4 and 40CDs/g-C3N4 achieved the highest degradation efficiency of 2,4-dichlorophenol (2,4-DCP) with 1.7 times higher than that of pure g-C3N4. Both projects successfully improved the properties of g-C3N4 by elongating the lifetime of photogenerated electrons and widening the visible light response. The M/g-C3N4 (M=Au, Ag and Pd) in 1st project fully degraded BPA within 70 min while CDs/g-C3N4 (2nd project) degraded 94% of 2,4-DCP within 120 min. Despite of higher photocatalytic efficiency in the 1st project, CDs/g-C3N4 was recommended for further exploration from the aspect of low production cost and high sustainability.